HOTS Outcomes in IPAS Learning Through the Discovery Learning Model for Fifth Graders of SDN Sukamulya - Erlina Erlina; Levina Putri; Heryani Heryani; Ina Setiawati; Mia Zultrianti Sari; M. Deni Ruhiyat; Ilham Nur Ikhsan; Frian Sumarya (Universitas Negeri Surabaya, 2026)
This study addresses the low higher-order thinking skills (HOTS) among elementary students by evaluating the implementation of the discovery learning model. It aims to determine the science and social sciences (IPAS) learning outcomes of fifth-grade students at SDN Sukamulya, analyze their obstacles in solving HOTS questions, and identify factors influencing their HOTS development. Employing a descriptive quantitative approach, this study involved 20 fifth-grade students. Data were collected via HOTS-oriented essays and observations, then analyzed using descriptive statistics and a one-sample t-test against the Minimum Mastery Criterion (KKM = 75). The results showed a mean post-test score of only 46.75, significantly below the KKM, with only 5% of students achieving mastery. Most students fell into the